2007
DOI: 10.1088/0957-4484/18/18/185710
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the optical spectra of an Ag/mesoporous SiO2nanostructure heat-treated in air and H2atmospheres

Abstract: Evolution of the various optical spectra of Ag nanoparticles dispersed in mesoporous SiO2 after heating alternately in H2 and air atmospheres has been investigated. It has been observed that, in accordance with alternate heat treatment in H2 and air, surface plasmon resonance (SPR) absorption of the Ag/mesoporous SiO2 nanostructure alternately appeared and disappeared and its Raman scattering spectra reversibly increased and decreased. In contrast, its photoluminescence (PL) spectra alternately disappeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…[14,15]. The mesoporous silica prepared in this way, whose pores are interconnected and open to ambient air, had a porosity of about 50%, a specific surface area of 560 m 2 and pore diameters mainly distributed in the range below 20 nm, determined by isothermal N 2 adsorption measurement, as described previously in Ref. [16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14,15]. The mesoporous silica prepared in this way, whose pores are interconnected and open to ambient air, had a porosity of about 50%, a specific surface area of 560 m 2 and pore diameters mainly distributed in the range below 20 nm, determined by isothermal N 2 adsorption measurement, as described previously in Ref. [16].…”
Section: Methodsmentioning
confidence: 99%
“…But on the other hand, it is seem that Ag has a special affinity with oxygen, 6 11 12 which was widely applied in catalysis field, and the mechanism of interaction between Ag and oxygen is still an unsolved and complex issue. In our previous studies, 2 13 significant change of SPR optical absorption has been reported due to the cooperation of the surface effect and interfacial influence among Ag, * Author to whom correspondence should be addressed. oxygen and SiO 2 substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such nanocomposites are typically prepared by the introduction of metal ions into the host followed by reduction processes that can be achieved for instance during heat treatment (HT) that subsequently leads to NP formation within the matrix. The optical properties of this type of materials are therefore dependent on glass thermal history and their assessment is central from both fundamental and technological standpoints [10,11]. In such a ground, optical absorption and photoluminescence (PL) spectroscopy have proved to be valuable tools in studying the evolution of the optical properties of silver-doped glasses through thermal treatment and the subsequent formation of NPs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, colloidal silver particles with their well-known plasmonic abilities, emerging in the waveguide during ion exchange with AgNO 3 , can significantly increase absorption and scattering of the fabricated waveguide and result in undesired fluorescence emission and high propagation losses. [14][15][16][17][18][19][20] Since the 1970s, ion-exchanged waveguides find their application in telecommunication and light distribution. Because of the nature of these applications, special substrates are used to fabricate single-mode waveguides at a specific wavelength.…”
Section: Introductionmentioning
confidence: 99%